2018
DOI: 10.13075/mp.5893.00577
|View full text |Cite
|
Sign up to set email alerts
|

Economic costs due to workers’ sick leave at wastewater treatment plants in Bulgaria

Abstract: Background: The compensatory mechanisms of social security include expenses for sick leave. The aim of the study is to determine the economic cost due to sick leave among workers in wastewater treatment plants (WWTPs), comparing with the same economic indicators of the National Social Security Institute (NSSI) in Bulgaria. Material and Methods: The sick leave of 111 workers at 3 WWTPs was studied in the period 2012-2014 on the grounds of registered absences from work due to temporary incapacity for work. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Considering that in Romania in 2021, the average gross salary was approximately 1166 EUR, the annual financial impact on the budget for only compensating long-term sick leaves was estimated at more than 40 million EUR/year. Many authors have shown that other costs should be added to this amount, such as health care expenditures, impacts on workers and their families or losses in productivity, which are difficult to estimate [ 39 ]. Other papers estimated that the indirect costs of work accidents and occupational diseases could be four to ten times greater than the direct costs.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that in Romania in 2021, the average gross salary was approximately 1166 EUR, the annual financial impact on the budget for only compensating long-term sick leaves was estimated at more than 40 million EUR/year. Many authors have shown that other costs should be added to this amount, such as health care expenditures, impacts on workers and their families or losses in productivity, which are difficult to estimate [ 39 ]. Other papers estimated that the indirect costs of work accidents and occupational diseases could be four to ten times greater than the direct costs.…”
Section: Discussionmentioning
confidence: 99%
“…14 25 Additional sources are less clear in defining a time frame, using vague descriptions such as 'until working capacity is covered'. 46 Following this, however, there is no information on the support given to those whose illness persists after their insurance entitlements expire. The degree of equity in social insurance schemes Results highlight large disparities in the populations that are adequately covered by social insurance.…”
Section: Conceptualising Ill Healthmentioning
confidence: 99%
“…Sick leave predicts mortality and work disability, 1,2 affects coworkers, 3 and causes economic costs 4 . The risk factors for sick leave reportedly include obesity, smoking, alcohol consumption, socioeconomic status, past sick leave, occupational stressors, and diabetes 5–10 .…”
mentioning
confidence: 99%
“…S ick leave predicts mortality and work disability, 1,2 affects coworkers, 3 and causes economic costs. 4 The risk factors for sick leave reportedly include obesity, smoking, alcohol consumption, socioeconomic status, past sick leave, occupational stressors, and diabetes. [5][6][7][8][9][10] Evidence suggests that intervention for high-risk workers, [11][12][13] workplace mental health training for managers, 14 participatory workplace improvement programs, 15 and other interventions 16 are effective for workers' health promotion.…”
mentioning
confidence: 99%